Análise morfológica de logomarca como estratégia no ensino do desenho geométrico - Reis, Francisco Carlos Cerqueira dos (2014)
Geometrical Design has been for many teachers a great challenge. On one side, we have rules that contribute to the disempowerment of such expertise in the Basic Education – Primary and Secondary Education. On the other side, an educational policy that brings back values to the Technical Professional Education, that in its turn is a major step to courses in the field of industry and infrastructure mostly, which demands proper qualification and expertise in order to expand competencies in the interpretation and development of graph sketches through Technical Design. The instructor stands in between such two edges restricted to a small number of actual professionals. In addition, due to the ever-downsizing labor area those professionals usually work as tutors in technical schools at both primary and secondary levels, since Geometrical Design is a discipline no longer mandatory in the referred school’s curriculum. On the other hand, such subject is not only present but also mandatory to schools that require some expertise in graph constructions, since it has been denied to students who have just graduated from middle school. From 2007 on, with the Professional Education implemented by the local federal government Technical Design instructors migrated to technical schools as means to qualify scholars in those institutes who had no opportunity to be previously skilled in Geometrical Design. This study main objective is to raise means to students’ autonomy development from the Instituto Federal da Bahia (IFBA), Salvador Campus, in the process of geometrical constructions from a logo study based upon a gap filling status in order to make Primary and Second Education less and less distant concerning the information upon Geometrical Design and Technical Design. Therefore, it was possible to identify the rank both Geometrical Design and Technical Design actually stand in the curriculum proposed by IFBA and analyze aspects related to expansion of competencies in Geometrical Design having a specific teaching strategy applied as a starting point.